Strategi Marketing Bank Syariah di Era Digital - Mariyam Ulfa; Iqbal Fasa, Muhammad (Jurnal Manajemen, Akuntansi dan Logistik (JUMATI), 2024)
This article discusses the marketing strategy of Islamic banks in the digital erd in the pontext of growing information technology and changing consumer behavior Islamic banks ust implement innovative and adaptive marketing strategies. By using digital platforms such as social media and mobile applications, Islamic banks can increase awareness of their products, expand their market, and build stronger relationships with their customers Digital transformation also creates opportunities for product and service innovation, but also faces challenges such as data security and privacy protection. This research provides insights into the importance of marketing strategies adapted to technological developments to improve the competitiveness of Islamic banks in an increasingly competitive market